The Analysis of Moral Values Found in “It Ends with Us” Novel by Colleen Hoover: English - Esi Marlini; Tahrun; Masagus Firdaus (Journal of English Development, 2024)
This study aimed to find moral values in the novel entitled “It Ends with Us” by Colleen Hoover. This study was used qualitative method where researcher conduct analysis of the intrinsic elements and moral values. Researcher used triangulation to enhance the accuracy of the study which focused on focus group discussion (FGD) and interviews. Based on the findings, and the results of FGD and interviews, it can be stated that solid intrinsic elements help construct the story very well, therefore it becomes interesting story for its readers in many countries. There are several moral values obtained from the novel, they are modesty, honesty, love and affection, bravery, sympathetic to others, kind-hearted, and sincerity. These moral values will be very important for students as the next generations of Indonesia. If these moral values are instilled into students, it is hoped that their morals will be improved gradually. Therefore, the target of the Mandate of the National Education System Law No. 20 of 2003 to develop students' potentials to become men of faith and fear of God Almighty, noble, capable, creative, independent, and democratic and accountable citizens can be obtained.